HUBUNGAN RETURN ON ASSET (ROA), QUICK RATIO (QR) DAN DEBT TO ASSET RATIO (DAR) TERHADAP HARGA SAHAM PADA PT BANK RAKYAT INDONESIA TBK PERIODE 2013-2023 - Darmawan Martawiharjo, Angga; Elfahmi, Ryan (Journal of Research and Publication Innovation, 2024)
This research aims to determine the Correlation of Return on Assets (ROA), Quick Ratio (QR) and Debt to Asset Ratio (DAR) on share prices at PT Bank Rakyat Indonesia Tbk Period 2013-2023. The method in this research is descriptive quantitative. The data analysis methods used include: Classic Assumption Test (Normality, Multicollinearity, Heteroscedasticity and Autocorrelation), Quantitative Test (Multiple Linear Regression, Correlation Coefficient and Coefficient of Determination), and Hypothesis Test (Pearson Bivariate Correlation Test/Product Moment). The results of this research indicate that partial Return On Assets (ROA) does not have a significant relationship with share prices at PT Bank Rakyat Indonesia Tbk. Because a significant value of 0.056 > 0.05 Ha1 is rejected and H01 is accepted. The Quick Ratio (QR) partially does not have a significant relationship with the share price at PT Bank Rakyat Indonesia Tbk. Because a significant value of 0.279 > 0.05 Ha1 is rejected and H01 is accepted. Debt to Asset Ratio (DAR) partially has a significant relationship with share prices at PT Bank Rakyat Indonesia Tbk. Because a significant value of 0.001 < 0.05. Ha1 is accepted and H01 is rejected. Simultaneously, Return On Assets (ROA), Quick Ratio (QR) and Debt to Asset Ratio (DAR) on Stock Prices have a very strong correlation with a correlation coefficient value of 83.3% and a determination value of 69.5%.